Study of bacteriological profile and sensitivity to various drugs in a case of wound dehiscence in tertiary care centre - Tripathi, Shashank Shekhar; Tripathi, Ankur; Singh, Rahul; Pandey, Himansha (International Surgery Journal, 2019)
Background: Surgical wound infection is a common post-operative complication causing significant post-operative morbidity and mortality, prolonged hospital stays and adds between 10-20% to hospital cost. Methods: This is a prospective study conducted in Department of General Surgery and Department of Microbiology, M.L.N. Medical College and Swaroop Rani Nehru Hospital, Allahabad. The study group comprised of all patients who underwent surgery during the period from October 2017 to September 2018 and were diagnosed with postoperative surgical site infection and wound dehiscence. Results: A total of 1640 patients were followed during one year of study. 540 (32.92%) patients were operated as emergency cases while 1100 (67.08%) were operated as elective cases. Conclusions: Wound dehiscence is a common surgical complication occurring in about 6.5% of surgical procedures. Emergency operative procedures are associated with higher incidence (16.67%) of wound dehiscence as compared to elective surgical procedures (1.67%). Male gender is more commonly associated with wound dehiscence especially in case of emergency surgical procedures with male to female ration of 1.67:1.Incidence of wound dehiscence increases with increasing age being maximum in older age group. Malnutrition is the most common risk factor present in surgical patients predisposing to wound dehiscence.